Consumers’ Use and Understanding of Food Label Information and Effect on their Purchasing Decision in Ghana; a Case Study of Kumasi Metropolis - J, Osei Mensah; D. R, Lawer; R, Aidoo (Asian Journal of Agriculture and Rural Development, 2012)
This study explored consumers’ use and understanding of food label information and the effect on their purchasing decision in the Kumasi Metropolis. It also investigated the association between socio-demographic factors and the use of food label, the understanding of the information read as well as the type of information sought. The study surveyed 250 consumers who were conveniently selected from five different sub-metros in the metropolis. Questionnaires were formulated to sample data and information from consumers on their use and understanding of Food Label Information. Results suggested that the sample was gender sensitive (57.6% male) with a modal aged group between 15-30 years (60.8%) who had never been married (54.0%), with a greater number who had tertiary education (36.4%) and earning low income between GH¢50-499 (61.6%). About 79.6% (n=199) of the respondents, recounted accessing food label information before purchase and they read the information occasionally (29.6%) during initial purchase (37.2%). Majority of the respondent said advertisement (31.6%) and price (31.2%) other than food label (10.0%) were the central stimuli to purchase a canned food product. Highly-educated, male consumers ) were those more likely to use various types of food label information than others. A positive relationship was observed between male, youthful (31-45) consumers and consumer who were never been married and their use and understanding of food label information.